Multiphoton time-domain fluorescence lifetime imaging microscopy: practical application to protein-protein interactions using global analysis - Barber, P; Ameer-Beg, S; Gilbey, J; Carlin, L; Keppler, M; Ng, T; Vojnovic, B (2009)
Förster resonance energy transfer (FRET) detected via fluorescence lifetime imaging microscopy (FLIM) and global analysis provide a way in which protein-protein interactions may be spatially localized and quantified within biological cells. The FRET efficiency and proportion of interacting molecules have been determined using bi-exponential fitting to time-domain FLIM data from a multiphoton time-correlated single-photon counting microscope system. The analysis has been made more robust to noise and significantly faster using global fitting, allowing higher spatial resolutions and/or lower acquisition times. Data have been simulated, as well as acquired from cell experiments, and the accuracy of a modified Levenberg-Marquardt fitting technique has been explored. Multi-image global analysis has been used to follow the epidermal growth factor-induced activation of Cdc42 in a short-image-interval time-lapse FLIM/FRET experiment. Our implementation offers practical analysis and time-resolved-image manipulation, which have been targeted towards providing fast execution, robustness to low photon counts, quantitative results and amenability to automation and batch processing. © 2008 The Royal Society.